2019
DOI: 10.1038/s41586-018-0868-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational periscopy with an ordinary digital camera

Abstract: Computational periscopy with an ordinary digital camera This work was made openly accessible by BU Faculty. Please share how this access benefits you. Your story matters.Computing the proportions of light arriving from different directions allows a diffusely reflecting surface to play the role of a mirror in a periscope. Such computational periscopy has previously depended on light travel distances being proportional to times of flight and thus has mostly been achieved with expensive, specialized ultrafast opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 35 publications
0
83
0
Order By: Relevance
“…There are also several contributions showing that it is possible to do NLOS imaging without picosecond scale time resolution or with non-optical signals: Inexpensive nanosecond time of flight sensors can be used to recover the hidden scene 33 , tracking can be performed using intensity based NLOS imaging 34 , occlusions are harnessed to recover images around a corner using regular cameras [35][36][37] , even describing the occlusion-aided method as a blind deconvolution problem without knowledge of the occluder 38 . Other approaches decode the hidden object from regular camera images by using a deep neural network trained with simulated data only 39 , or use acoustic 40 or long-wave infrared 41 signals to image around the corner.…”
Section: Discussionmentioning
confidence: 99%
“…There are also several contributions showing that it is possible to do NLOS imaging without picosecond scale time resolution or with non-optical signals: Inexpensive nanosecond time of flight sensors can be used to recover the hidden scene 33 , tracking can be performed using intensity based NLOS imaging 34 , occlusions are harnessed to recover images around a corner using regular cameras [35][36][37] , even describing the occlusion-aided method as a blind deconvolution problem without knowledge of the occluder 38 . Other approaches decode the hidden object from regular camera images by using a deep neural network trained with simulated data only 39 , or use acoustic 40 or long-wave infrared 41 signals to image around the corner.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method requires hardware (mostly consumer-grade electronics) that is far less expensive than that required for the TOF-based NLOS imaging [16,24,25,26,27,33,37,39,40], and the method is more robust than the memoryeffect based imaging techniques that have a limited field-ofview [11,21]. Moreover, a recent publication [31] also uses only ordinal digital cameras but would require very specific scene setup (an accidental occlusion) to obtain better performance.…”
Section: Related Workmentioning
confidence: 99%
“…Bouman et al [7] showed that obstructions with edges, e.g., walls, can be exploited as a camera that reveals the NLOS scene beyond them. Saunders et al [8] proposed a passive NLOS imaging which requires only a single image captured with an ordinary camera to recover a partially hidden scene and the position of an opaque object in the NLOS scene. Beckus et al [9] also proposed a passive NLOS imaging by a multi-modal fusion of the intensity and the spatial coherence function.…”
Section: Passive Nlos Imagingmentioning
confidence: 99%